COMPARATIVE ASSESSMENT OF HEAVY METALS IN AJIWA AND JIBIA IRRIGATION DAMS OF KATSINA STATE, NIGERIA - Musa, Mohammed Salisu; Dagari, M. S.; Umar, A.; Shafiu, I. M. (FUDMA JOURNAL OF SCIENCES, 2020)
Concentrations of some heavy metals in water samples from Ajiwa and Jibia irrigation Dams of Katsina State were determined using Micro Plasma Atomic Emission Spectroscopy (MP-AES). The water samples were analyzed to determine zinc (Zn), cadmium (Cd), copper (Cu), nickel (Ni), cobalt (Co), lead (Pb), manganese (Mn) and chromium (Cr) contents. The mean concentrations (mg/L) of the heavy metals in water samples of Ajiwa and Jibia dams respectively were: zinc (1.00±0.010, 0.04±0.010); cadmium (0.03±0.010, ND); copper (0.03±0.010, ND); lead (0.01±0.001, 0.02±0.001); manganese (0.21±0.001, 0.18±0.001); and chromium (0.05±0.001, 0.05±0.001), while nickel and cobalt were not detected in both samples. The P value (0.60314) indicates that there is no significant difference in the metal contents between the water bodies. Assessment of these metals in both water samples shows that none of the metals was above maximum permissible limit. However, cadmium and chromium concentrations were found to be at the maximum permissible level allowed in irrigation water. These findings therefore indicated that, the two water bodies are suitable and safe for irrigation purposes